COACH AS AN INNOVATIVE TECHNOLOGY FOR IMPROVING THE PROFESSIONAL SKILL OF A TEACHER - Могиляста, Світлана (Modern engineering and innovative technologies, 2023)
The article analyzes the peculiarities of the use of coaching technology for the formation of self-educational competence of teachers. The effectiveness of using coaching to activate students’ cognitive motivation, encourage self-study and professional se